A Correlational Study of Problem-Solving and Collaborative Skills in Learning the Circulatory System - Nina Irawan; Dios Sarkity; Trisna Amelia (Jurnal Kiprah Pendidikan, 2026)
is study aimed to examine the relationship between students’ problem-solving skills and their collaborative skills in learning the circulatory system. The research employed a quantitative correlational design. The participants were 64 eleventh-grade students selected through cluster random sampling. Data were collected using a written test and classroom observation. Problem-solving skills were assessed through essay-type questions, while collaborative skills were evaluated using an observation checklist. The relationship between the two variables was analyzed using Spearman’s Rank correlation test. The findings revealed that there was no significant correlation between students’ problem-solving and collaborative skills in circulatory system learning. These results suggest that 21st-century competencies, particularly problem-solving and collaboration, do not necessarily develop in a linear or directly associated manner. Therefore, instructional strategies should be designed to foster each skill independently, taking into account their distinct characteristics to ensure more effective competency development.